2003
DOI: 10.1055/s-2003-38400
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Oral Creatine-Pyruvate Supplementation in Cycling Performance

Abstract: A double-blind study was performed to evaluate the effects of oral creatine-pyruvate administration on exercise performance in well-trained cyclists. Endurance and intermittent sprint performance were evaluated before (pretest) and after (posttest) one week of creatine-pyruvate intake (Cr(pyr), 2 x 3.5 g x d-1, n = 7) or placebo (PL, n = 7). Subjects first performed a 1-hour time trial during which the workload could be adjusted at 5-min intervals. Immediately they did five 10-sec sprints interspersed by 2-min… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 33 publications
0
21
0
Order By: Relevance
“…The present study supports that finding because Cr supplementation attenuated the rise in muscle energy imbalance during the performance ride but did not affect the ability to increase power output during approximately 15 min of exercise following 45 min of exercise at approximately 80% V O 2peak . We anticipated that Cr supplementation would not influence endurance exercise performance because others have found no effect of Cr supplementation on prolonged (8 -60 min) exercise performance (1,2,28). It should be noted, however, that a type 1 error may exist in our performance data because a small number of individuals was studied using a performance measure with a relatively large coefficient of variation of 3.5%.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The present study supports that finding because Cr supplementation attenuated the rise in muscle energy imbalance during the performance ride but did not affect the ability to increase power output during approximately 15 min of exercise following 45 min of exercise at approximately 80% V O 2peak . We anticipated that Cr supplementation would not influence endurance exercise performance because others have found no effect of Cr supplementation on prolonged (8 -60 min) exercise performance (1,2,28). It should be noted, however, that a type 1 error may exist in our performance data because a small number of individuals was studied using a performance measure with a relatively large coefficient of variation of 3.5%.…”
Section: Discussionmentioning
confidence: 98%
“…These improvements are thought to be caused largely by the increases in muscle total Cr, and particularly Cr phosphate, which makes a major contribution to adenosine triphosphate (ATP) resynthesis during such exercise (7,8). On the other hand, Cr supplementation does not appear to influence endurance exercise performance (1,2,28). Indeed, recently it was shown that 1-h time trial exercise performance is not influenced by Cr supplementation in trained cyclists (2).…”
mentioning
confidence: 99%
“…One of the most widely used supplements for ergogenic purposes is creatine (Lawler et al, 2002). Creatine, when supplemented for short-time periods, improves performance during repeated bouts of high intensity exercise (review in Mujika and Padilla, 1997;Kreider, 2003), while there is a lack of an ergogenic effect of creatine supplementation in a variety of endurance exercise protocols (van Loon et al, 2004;Van Schuylenbergh et al, 2003;Izquierdo et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…8,29,55,56 Performance in running sprints was improved in most, 8,14,25,29 but not all studies, 40 and inconsistent results have been observed for cycling sprint performance, with benefits observed in several studies, 7,11,15,16,47,58 while not in others. 12,17,49,52,53 Cr supplementation generally has not been associated with improvements in endurance exercise performance, 16,29,52 or a reduction in muscle damage with high-intensity exercise. 44 Some of the discrepancies between study results may be attributable to differences in study design, including the sex, age, and training status of the subjects (untrained individuals versus elite athletes), the sport for which athletes were trained, Cr dose and duration of supplementation (3 days-12 weeks), and the exercise tests used to assess benefits.…”
Section: Effects Of Creatine Supplementation On Performancementioning
confidence: 98%